2009
DOI: 10.1111/j.1752-1688.2009.00353.x
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Watershed Subdivision and Soil Data Resolution on SWAT Model Calibration and Parameter Uncertainty1

Abstract: Impact of watershed subdivision and soil data resolution on Soil Water Assessment Tool (SWAT) model calibration and parameter uncertainty is investigated by creating 24 different watershed model configurations for two study areas in northern Indiana. SWAT autocalibration tool is used to calibrate 14 parameters for simulating seven years of daily streamflow records. Calibrated parameter sets are found to be different for all 24 watershed configurations, however in terms of calibrated model output, their effect … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
51
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 81 publications
(56 citation statements)
references
References 51 publications
5
51
0
Order By: Relevance
“…Figure 4 illustrates that the mean of drainage density tends to decrease as the mean of sub-watershed area increases, while the average of longest flow length within each subwatershed increases. This result is similar to that found by Kumar and Merwade (2009). Further, we find that the function of averaged drainage density and averaged longest flow length versus averaged basin areas follows a power law.…”
Section: Changes In Watershed Attributessupporting
confidence: 80%
See 3 more Smart Citations
“…Figure 4 illustrates that the mean of drainage density tends to decrease as the mean of sub-watershed area increases, while the average of longest flow length within each subwatershed increases. This result is similar to that found by Kumar and Merwade (2009). Further, we find that the function of averaged drainage density and averaged longest flow length versus averaged basin areas follows a power law.…”
Section: Changes In Watershed Attributessupporting
confidence: 80%
“…For example, it has been shown that subwatershed size affects the determination of peak flow magnitude and that the effect changes for different storm types (Ghosh and Hellweger, 2011). Some researchers claim contradictory results regarding the effect of sub-watershed size on determining peak flow magnitudes (Ao et al, 2003;Kumar and Merwade, 2009;Ghosh and Hellweger, 2011). Some have reported that larger sub-watersheds decrease flood peak (Muleta et al, 2007), while others have concluded that the effect can be neglected (Cleveland et al, 2009;Chen et al, 2011).…”
Section: Published By Copernicus Publications On Behalf Of the Europementioning
confidence: 99%
See 2 more Smart Citations
“…An obvious approach is to divide the watershed into its natural sub-watersheds, thus preserving the watershed's natural boundaries, flow-paths and channels for realistic water routing [23][24][25][26][27][28][29]. The concepts of critical source area [30][31][32][33][34][35][36], threshold drainage area [37] and aggregated simulation area [38] have also been used to delineate sub-watersheds within semi-distributed models. Moving from semi-to fully-distributed modelling, more detailed concepts are employed, such as grid elements, Representative Elementary Areas (REAs) and Representative Elementary Watershed (REW).…”
Section: Overview Of Schematization and Parameterization Approaches Imentioning
confidence: 99%